2023
DOI: 10.1002/sstr.202200308
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Ammonia Synthesis from Nitrate Catalyzed by Au/Cu with Enhanced Adsorption Ability

Abstract: The traditional method for synthesizing NH3 is the Haber–Bosch process which results in high‐fuel consumption and environmental pollution. Therefore, ecofriendly electrochemical synthesis of NH3 through nitrate (NO3−) reduction is a good choice. Herein, an integral Au/Cu electrode to catalyze NO3− reduction to NH3 is introduced. The catalyst exhibits not only the highest NH3 yield rate (73.4 mg h−1 cm−2) up to now but also a very high Faradaic efficiency of 98.02% at −0.7 V at room temperature. It is commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Additionally, at room temperature and pressure, nitrogen gas (N 2 ) has a low solubility in electrolytes due to its non-polar characteristics and the reaction kinetics at the gas-liquid-solid interface are slow. 1,[10][11][12][13][14] In contrast, the electrocatalytic nitrate reduction reaction (NO 3 RR) for ammonia production is thermodynamically more viable. This is because NO 3 RR involves a higher theoretical electrode potential (NO 3…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, at room temperature and pressure, nitrogen gas (N 2 ) has a low solubility in electrolytes due to its non-polar characteristics and the reaction kinetics at the gas-liquid-solid interface are slow. 1,[10][11][12][13][14] In contrast, the electrocatalytic nitrate reduction reaction (NO 3 RR) for ammonia production is thermodynamically more viable. This is because NO 3 RR involves a higher theoretical electrode potential (NO 3…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ammonia has the potential to be a promising carrier for hydrogen energy in the future. 1 As both a fertilizer and neutralizer, ammonia has been widely used in various industries, including wastewater treatment, leather, paper, food, and beverage. Currently, the main method for the industrial production of ammonia is the Haber–Bosch process (H 2 + N 2 → NH 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable endeavors have been directed toward creating advanced metal electrode materials by incorporating heteroatoms/heterojunctions, [41][42][43] and introducing noble metals. 7,44,45 Recent investigations have demonstrated that the inclusion of vacancy sites, such as selenium-vacancy, S-vacancy, and oxygen vacancy (OV), within materials based on metal oxides presents a straightforward and efficient approach for boosting their catalytic effectiveness. [46][47][48][49][50][51] The incorporation of OVs as a strategy has found extensive application in diverse fields, including the OER, 52,53 ORR, 54,55 CO 2 RR, 56,57 HER 58,59 and NRR, 60,61 supercapacitors, 62 and batteries, 63,64 with impressive results showcasing their remarkable ability to adsorb and activate various molecules like O 2 , H 2 O, and H 2 , among others.…”
mentioning
confidence: 99%